Wood-steel connections (W-S-W) in double shear at room and high temperatures - Silva, Lino Daniel Soares (2020)
The present master thesis was developed in Master’s degree in Mechanical Engineering on the branch of Mechanical Constructions. The main purpose of this thesis is to study the behavior of wood connections (protected and unprotected) of the wood-steel-wood type (W-S-W) under double shear, with dowels as connectors and a steel plate as central member at room temperature and high temperatures. For this, it was required to use an analytical and numerical method and, subsequently, its comparison was performed. The analytical method, based on simplified equations from Eurocode 5, parts 1-1 and 1-2, was used in order to design the mechanical and thermal behavior of wood connections with steel dowels. The numerical methodology, based on the finite element method with ANSYS Academic Mechanical® software, was used in order to obtain computational thermal simulations, which allow verifying the effect of the connectors, the steel plate and the gypsum boards on the char layer growing effect. The comparison between analytical and numerical methods provides additional information in order to certify designers and professionals that this type of connection is safe to use. For each studied connection, different dowel diameters and applied loads were used, both at room temperature and under fire exposure. Loads of 10, 15 and 20 kN were admitted, with dowels diameters of 6, 8 and 10 mm. The re-arrangement of the connectors was kept constant in three columns but different lines in all designed connections. Three different types of wood were used, GL20h, GL24h, and GL32h. The fire action in the connection was imposed by the standard curve ISO834. In the protected connections, two types of insulators were used, gypsum types A and F, in order to protect the connection during 60 min under fire conditions.